Faces and places [biomedical MRI pioneer]. - Szeto, A.Y.J.
MRI is now routinely used for medical diagnostics due to several inherent advantages over other imaging modalities. One major advantage of MRI is its safety and image quality. In contrast to conventional X-ray computer tomography, MRI does not use ionizing radiation so its use need not be limited by exposure concerns.
Keywords: Biomedical MRI; Image quality; Imaging modalities; Medical diagnostics